2018
DOI: 10.1002/em.22268
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Fungicide Captan Induces DNA Base Alterations and Replicative Stress in Mammalian Cells

Abstract: The classification of the fungicide captan (CAS Number: 133–06‐2) as a carcinogen agent is presently under discussion. Despite the mutagenic effect detected by the Ames test and carcinogenic properties observed in mice, the genotoxicity of this pesticide in humans is still unclear. New information is needed about its mechanism of action in mammalian cells. Here, we show that Chinese Hamster Ovary (CHO) cells exposed to captan accumulate Fpg‐sensitive DNA base alterations. In CHO and HeLa cells, such DNA lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Two of the most common cancers associated with pesticide use include non-Hodgkin lymphoma and leukemia [6,8]. While the etiology and pathogenesis of MM are still under investigation, recent studies have shown an elevated risk of MM with pesticide use [2,6,9-10]. For example, one case-control study collected extensive information, including occupational history from 573 persons with newly diagnosed multiple myeloma, and developed a job-exposure matrix for pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the most common cancers associated with pesticide use include non-Hodgkin lymphoma and leukemia [6,8]. While the etiology and pathogenesis of MM are still under investigation, recent studies have shown an elevated risk of MM with pesticide use [2,6,9-10]. For example, one case-control study collected extensive information, including occupational history from 573 persons with newly diagnosed multiple myeloma, and developed a job-exposure matrix for pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a great deal of debate worldwide regarding its toxicity. In the United States, the EPA or environmental protection agency classifies captan as “not likely carcinogenic to humans,” whereas the European commission classifies it as “suspected of causing cancer” [10]. Due to this controversy and given its extensive use, several recent studies have investigated the potential toxicity of captan and demonstrated a consistent increased risk of MM with captan exposure [5,10-12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HeLa or U2OS cells were treated with CDT for 16 or 24 h, respectively, before sequential pulse labeling with 50 µM CldU (5-chlorodeoxyuridine, Sigma-Aldrich), then 100 µM IdU (5 iododeoxyuridine, Sigma-Aldrich) for 20 min each, followed by a chase with 200 µM thymidine (Sigma-Aldrich) for 1 h. Cells were then collected and DNA fiber assays were performed as described previously (Fernandez-Vidal et al, 2019). IdU and CldU were detected with monoclonal mouse (1/50, BD347583, Becton Dickinson) and rat anti-BrdU antibodies (1/75, OBT0030G, Bio-Rad), respectively, and subsequently single-strand DNA with mouse antibody (1/50, MAB3034, Millipore).…”
Section: Dna Fiber Assaymentioning
confidence: 99%
“…Pesticides have selective and targeted activity against mycopathogens and crop weeds. However, the selectivity of pesticide activity is not absolute: the evolutionary conservatism of many molecular-cellular events determines the activity of pesticides with respect to non-target organisms [16,17,18,19,20,21,22]. In this regard, cytogenetic studies of pesticides with respect to cereal crops, which are the main source in the nutritional structure of the world's population, are very important.…”
Section: Introductionmentioning
confidence: 99%